Effects of DSB on market clearing price - Bai, J.; Gooi, H. B.; Strbac, G.; Venkatesh, B. (2006)
In this paper, a market clearing study is examined by incorporating demand-side bidding (DSB) where customers are allowed to submit load reduction bids. The relationship between the bulk purchase and load reduction bids is presented. A Lagrangian Relaxation optimization method is developed to simultaneously clear generation and demand reduction bids, while maximizing the overall benefits for market participants. Case studies performed demonstrate that, in general, DSB aids in reducing system marginal price (SMP) but there are times where the value of DSB is affected when offer bids of inflexible units are replaced by higher DSB bids. The results also indicate that while load recovery addresses customer needs, it reduces the value of DSB. Copyright (c) 2005 John Wiley & Sons, Ltd.